FIRST FIND OF PECTOLITE IN MANGANESE DEPOSITS OF THE USSR - Kalinin V.V.; Marsiy I.M.; Troneva N.V. (My University, 1990)
Pectolite NaHCa2[Si3O9] has been known since the early 19th century. It is found in igneous rocks, in various parts of the world, including basalts, dolerites, and largely in alkalic rocks. We found pectolite in manganese ores at the Ir-Nimi deposit. It is located on the north flank of the Taykan Range, on the divide between the Nimi and Ir rivers, right-bank tributaries of the Uda, which empties into the Sea of Okhotsk. A quantitative X-ray microanalysis was performed with a Cameca MS-46 microprobe. The analytical lines were the characteristic X-ray lines of all the elements investigated. Pectolite and the minerals of the associated alkalic and alkaline-earth mineralization, taykanite, namansilite, a hydrosilicate of Na, Ba and Mn, minerals of the amphibole group and the late stage of development of the Dzhagdy eugeosyncline. These minerals were produced by alkaline hydrothermal solutions that arose during differentiation of a basaltoid magma in the late Mesozoic.
Keywords: Mesozoic; Mesozoic; Мезозой